Linear differential equations with analytic coeffi cients of [p, q]# order in the unit disc - Belaïdi, BENHARRAT; Latreuch, ZINELAÂBIDINE (Sarajevo J. Math, 2013)
In this paper, we investigate the complex higher order linear differential equations in which the coefficients are analytic functions in the unit disc of [p, q]-order. We obtain several theorems about the growth and oscillation of solutions of differential equations.
Keywords: Linear differential equations, [p, q]-order; analytic function; hyper-order; exponent of convergence of the sequence of distinct zeros